Analysis of the payment discipline of trade-licence holders regarding social insurance contributions in the Slovak Republic - Tatiana Hajdúková; Edita Lukáčiková (Financial Internet Quarterly, 2024)
Guarantee of autonomy and stability of economic subjects from the government can be consid- ered an important gauge of state security. Due to the financial, migration and energy crisis, we can observe a notable increase of social problems, which gives more importance to the policy for social security of the population. In this article we address the ongoing problem of an excessively high number of debts owed to the Slovak Social Insurance Agency in recent years. The social security system for trade-licence holders, its financing and the method of enforcement are briefly characterised. The development of the payment/non-payment of taxes and levies to the Social Insurance Agency is tracked against the background of legislative changes. In the conclu- sion, the ineffectiveness of selected legal provisions and processes of exacting taxes and social security contributions is evaluated in terms of their impact on the financial disciplines of trade- licence holders in the Slovak Republic. Severity of the deficit in money collected on social insur- ance poses a threat in several areas, such as providing social security to all citizens in some re- quired quality as guaranteed by the government, or sustainability of the public finance which poses a risk for the whole economic security of the country.
Keywords: H63; J28; K22; 330; Public Finance; Not Paying Taxes and Insurance; Debtors; Social Insurance